Editorial: History of Family Pedagogy. Creators, Ideas, Concepts - Władysława Szulakiewicz (Jesuit University Ignatianum in Krakow, 2024)
Scientific interest in various aspects of the family has a long history, with specialists across many academic disciplines undertaking and continuing to pursue research in this area. The recognition of scientific achievements in family pedagogy is evident in the establishment of family sciences as a distinct discipline within the framework of the Council for Scientific Excellence, now in its second term of operation (2024-2027). Notably, the Council's Resolution of February 13, 2023, which addressed changes in the classification of disciplines and fields as specified in the regulations pursuant to Article 5 (3) of the Law on Higher Education and Science of July 20, 2018, listed pedagogy as one of the disciplines from which family sciences was separated.